Patient‐reported outcomes of blue‐light flexible cystoscopy with hexaminolevulinate in the surveillance of bladder cancer: results from a prospective multicentre study. (11th August 2018) - Smith, Angela B.; Daneshmand, Siamak; Patel, Sanjay; Pohar, Kamal; Trabulsi, Edouard; Woods, Michael; Downs, Tracy; Huang, William; Taylor, Jennifer; Jones, Jeffrey; O'Donnell, Michael; Bivalacqua, Trinity; et al.
Abstract : Objective: To evaluate blue‐light flexible cystoscopy (BLFC) with hexaminolevulinate in the office surveillance of patients with non‐muscle‐invasive bladder cancer with a high risk of recurrence by assessing its impact on pain, anxiety, subjective value of the test and patient willingness to pay. Materials and Methods: A prospective, multicentre, phase III study was conducted during which the Patient‐Reported Outcomes Measurement Information System (PROMIS) Anxiety, Pain and 'Was It Worth It' questionnaires were administered at baseline, after surveillance with BLFC and after resection for those referred to the operating room. Comparisons of scores were performed between groups. Results: A total of 304 patients were enrolled, of whom 103 were referred for surgical examination. Of these, 63 were found to have histologically confirmed malignancy. Pain levels were low throughout the study. Anxiety levels decreased after BLFC (∆ = −2.6), with a greater decrease among those with negative pathology results ( P = 0.051). No differences in anxiety were noted based on gender, BLFC results, or test performance (true‐positive/false‐positive). Most patients found BLFC 'worthwhile' (94%), would 'do it again' (94%) and 'would recommend it to others' (91%), with no differences based on BLFC results or test performance. Most patients undergoing BLFC (76%) were willing to pay out of pocket. Conclusions: Anxiety decreased after BLFC in patients with negative pathology, including patients with false‐positive results. Most of the patients undergoing BLFC were willing to pay out of pocket, found the procedure worthwhile and would recommend it to others, irrespective of whether they had a positive BLFC result or whether this was false‐positive after surgery.